2020
DOI: 10.1101/2020.11.24.20237644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess mortality across regions of Europe during the first wave of the COVID-19 pandemic – impact of the winter holiday travelling and government responses

Abstract: BackgroundThis aggregated population study of 219 regions in 11 European countries investigated the effect of the seemingly quasi-randomly assigned school winter holiday week on excess mortality associated with the COVID-19 pandemic during spring 2020. A secondary aim was to evaluate the impact of stringency and timing of the government responses to the early inflow of infected cases.MethodsRegional data on mortality week 14-23 in 2020 compared with the same period 2015-2019 were retrieved from Eurostat and na… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Included studies are described in Table 1, grouped by exposure type and study design. Of these, 32 studies(14,15,1821,23,24,26,2940,4244,46–53) reported the effect of school closures on community transmission of SARS-CoV-2, 11(16,22–25,27,28,35,4345) examined school reopening, and 3(16,17,41) investigated the effect of school holidays. Some studies considered more than one exposure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Included studies are described in Table 1, grouped by exposure type and study design. Of these, 32 studies(14,15,1821,23,24,26,2940,4244,46–53) reported the effect of school closures on community transmission of SARS-CoV-2, 11(16,22–25,27,28,35,4345) examined school reopening, and 3(16,17,41) investigated the effect of school holidays. Some studies considered more than one exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The studies on school reopening generally reported on single countries (Germany (n=2)(22, 28), USA (n=1)(25), Switzerland (n=1)(43), Belgium (n=1)(27), Israel (n=1)(45), Italy (n=1)(23)), but one reported discrete estimates for three countries (Denamrk, Germany and Norway)(44), two pooled data from multiple countries globally(16, 35), and one pooled data from multiple European countries(24). Of the three school holiday studies, one reported on Germany(41), one pooled data from 24 countries globally(16), and one pooled data from multiple European countries(17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations